Looking Back the Most Beautiful Molecule C60 after Quarter Century of Discovery Insert - Ōsawa, Eiji (Вісник НАН України, 2012)
On the occasion of silver anniversary of the C60 discovery, the present situation of C60 research is briefly analyzed from three distinct angles: molecule, solid and nanoparticle. With regard to molecular angle, the long pending problem of formation mechanism is almost solved by molecular dynamics approach hinted by Prigogine’s nonequilibrium thermodynamics. The C60 research is at the moment most active in chemistry, and some of the recent results are discussed here. Though C60 is closer to molecule than to the smallest nanoparticle in its outlook, a big future seems hidden in its application in nanotechnology.